2019
DOI: 10.1002/hep.30118
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of Starvation‐Stimulated Hepatic Autophagy

Abstract: Two central functions of the lysosomal degradative pathway of macroautophagy (hereafter referred to as autophagy) are to provide cells with metabolic substrates for energy generation in times of limited nutrients and act as a quality control mechanism to remove damaged or aged cellular components. Recent investigations have demonstrated that both functions regulate normal hepatic physiology and when impaired contribute to the pathophysiology of liver disease. The full spectrum of autophagy's metabolic function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…Additionally, researches have also shown that Ca 2+ plays an indispensable role in the autophagy process [ 157 ]. Autophagy is a smart evolutionary process of transformation of eukaryotes [ 158 , 159 ].…”
Section: Calcium-based Nanomaterials For Cancer Diagnosis and Therapymentioning
confidence: 99%
“…Additionally, researches have also shown that Ca 2+ plays an indispensable role in the autophagy process [ 157 ]. Autophagy is a smart evolutionary process of transformation of eukaryotes [ 158 , 159 ].…”
Section: Calcium-based Nanomaterials For Cancer Diagnosis and Therapymentioning
confidence: 99%
“…Indeed, autophagy has been considered as an emerging metabolic regulatory pathway in skeletal muscle, and its role in skeletal muscle metabolism and atrophic diseases has been extensively studied [ 212 , 213 ]. In skeletal muscle autophagy signal transduction, mTOR, AMPK, AKT and FoxO3, as important central trophic effectors, regulate autophagy process according to nutritional status, and their interaction with OGT is inseparable [ 214 , 215 , 216 , 217 ]. Given the critical role of O -GlcNAcylation in these processes, O -GlcNAcylation may affect autophagy flux and proteostasis to regulate skeletal muscle mass and proteolysis [ 206 ].…”
Section: O -Glcnacylation Autophagy and Skeletal Muscle Path...mentioning
confidence: 99%
“…Meanwhile, Caenorhabditis elegans bearing null mutations of ogt-1 or oga-1 increases autophagy under food deprivation-induced starvation [ 224 , 225 ]. Genetic ablation of OGT in mouse livers also affects autophagic flux under similar deprivation [ 25 , 216 ]. For example, the reduction of OGT in Drosophila was associated with the increase of autophagy-related gene (ATG) product and autophagy lysosomes [ 226 ].…”
Section: O -Glcnacylation Autophagy and Skeletal Muscle Path...mentioning
confidence: 99%
“…Autophagy is initiated by formation of the isolation membrane (double‐membrane phagophore), and the extended phagophore engulfs target organelles and transports them to lysosomes for degradation 7,8 . After lysosomal degradation, recycling replenishes the cell with nutrients 9,10 . Our interest is in the association of autophagy with liver diseases 11 .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 After lysosomal degradation, recycling replenishes the cell with nutrients. 9,10 Our interest is in the association of autophagy with liver diseases. 11 For example, we found that autophagy is an independent risk factor of recurrence after patients with HCC with large tumors undergo surgery.…”
Section: Introductionmentioning
confidence: 99%